(untitled) (Ágora UNLaR, 2019)
En “Generative Translation in Spicer, Gelman and Hawkey”, Lisa Bradford (2013) explica que los traductores intentan “transplantar un texto a un nuevo paisaje lingüístico de manera exitosa” y que pueden lograrlo mediante un estilo de traducción generativa, una poética que funciona para revelar y reavivar la articulación original y producir, al mismo tiempo, un nuevo texto (p.2). A partir de una lectura comparativa de “Slowly: a plainsong from an older woman to a younger woman”, de Judy Grahn, y “Meditations on the Declension of Beauty by the Girl with the Flying Cheek-bones”, de Marlene Nourbese Philip, este estudio plantea las problemáticas que surgen de la traducción de estos textos al castellano. Grahn, poeta estadounidense, es conocida por sus producciones de tinte política y sus contribuciones al movimiento lesbiano-feminista. Philip, poeta caribeña, describe en sus poemas las experiencias de la mujer negra y las cuestiones de pertenencia y lenguaje que derivan de la etapa colonial y postcolonial. Los textos seleccionados son, sin duda, claras exposiciones de la ideología y posición de estas poetas y tratan la cuestión de la identidad mediante un juego interesante de sonidos y repeticiones, la fragmentación, la dilación y el juego de palabras. Dadas estas características, un tipo de traducción generativa que permita producir conversaciones con los textos originales y generar nuevas imágenes se transforma en una opción interesante. THE POETRY OF JUDY GRAHN AND MARLENE NOURBESE PHILIP: ISSUES OF IDENTITY AND PRACTICES OF GENERATIVE TRANSLATION Abstract In “Generative Translation in Spicer, Gelman and Hawkey”, Lisa Bradford (2013) explains that translators try to “successfully transplant a work into a new language-land in order to share and perpetuate its beauty”, however, not all of them “strive to clone the source text, preferring rather to cultivate it by means of generative translation”, a “translational poetics that functions to reveal and revive the original articulation while producing an entirely fresh work of art” (p.2).The comparative reading of “Slowly: a plainsong from an older woman to a younger woman”, by Judy Grahn, and “Meditations on the Declension of Beauty by the Girl with the Flying Cheek-bones”, by Marlene Nourbese Philip, allows analyzing some of the issues that become evident when attempting different forms of translation of these texts into another language. Grahn, American poet, is wellknown for her political writings and her contributions to the lesbian-feminist movement. Philip, Caribbean poet, describes in her poems the experiences of the woman of color during and after colonial and postcolonial times. The selected poems are, without a doubt, clear examples of these poets’ ideology and deal with questions of identity through the interesting mingling of the use of repetition, fragmentation, language play and delay. The option of a type of generative translation that allows conversations with the original texts and the generation of new images is indeed a valid option to consider. Key Words: generative translation- ideology-language play- delay-fragmentation